Clinical characterization of Colombian families with frontotemporal dementia due to the MAPT P397S mutation. (31st December 2021) - Zuluaga‐Castaño, Yesica; Aguillon, David; Rassi, Sofia; Zuluaga, Maria; Gómez‐Henck, Clara; Lopera, Francisco; Quiroz, Yakeel T.
Abstract: Background: Mutations in the microtubule associated protein tau (MAPT) gene located in chromosome 17 have been associated with frontotemporal dementia (FTD). The novel mutation Pro397Ser, with an autosomal dominant inheritance pattern has been recently reported in Spain (Borrego‐Écija et al., 2019). The Group of Neuroscience of the University of Antioquia in Colombia has identified several families with mutations leading to FTD. Here we present the initial clinical characterization of individuals carrying the MAPT P397S mutation. Method: A total of 30 family members were included (15 carriers and 15 non‐carriers, 18 – 76 years old). All participants underwent a comprehensive neurological and neuropsychological evaluation. They also completed self‐reported measures of depression and behavioral symptoms. Mann‐Whitney tests were used to test between‐group differences in cognitive measures. Spearman correlations were used to examine associations among outcome measures and age. Result: Mean age was 48.7 years (SD 16.4), and mean education was 10.7 years (SD=4.56). Six carriers were classified as cognitively impaired (MCI= 3, moderate/severe dementia= 3). Mean age of clinical was 50 years. Initial symptomatology was predominantly behavioral (disinhibition, aggressiveness, loss of empathy, compulsiveness, dietary changes) followed by loss of executive function, memory, language skills and decline in ADLs in affected individuals. Structural MRIs showed frontotemporal lobar degeneration in all impaired carriers, and additional bilateral hippocampal atrophy with left predominance in two of them. The cognitive profile of carriers was characterized by lower scores in measures of executive function, semantic processing and short‐term memory loss. Cognitively unimpaired carriers had statistically significant worse performance on the INECO Battery, a measure of executive function, compared to non‐carriers, several years prior to their clinical onset. Conclusion: Initial findings showed that the clinical profile of Colombian families with the MAPT‐P397S novel mutation is characterized by executive dysfunction, behavioral changes, semantic language alterations and memory loss. Findings suggest that the INECO Battery may be a sensitive tool to detect subtle changes in executive function in cognitively unimpaired carriers of this mutation. Longitudinal follow‐up of these individuals will be important to better characterize the disease progression from preclinical to clinical stages. Future studies should consider adding neuroimaging and other biomarker measures.